Malaria: A Driving Force to the Emergence and the Global Spread of Antibiotics Resistance - O. Makanjuola Rasheed; Ishaleku David (International Journal of Global Health, 2025)
Malaria and bacteraemia are significant public health concerns and economic threats. In Africa, the intensity for simultaneous transmission and co-infection of Plasmodium spp and other bacteria pathogens are extremely high. It is believed that malaria suppress the immune system and enable the translocation of bacteria in the gastrointestinal tract to other cellular compartments in the body. Some of the factors that contributed to the co-emergence of these pathogens are poor access to clean water, sanitation and hygiene (WASH), poor infection control measures, inefficient health care systems. In addition, the similarities in the clinical signs and symptoms of these febrile diseases and the fact that the etiologic diagnostic testing can be complex, costly, and limited are the reasons why clinicians in resource-constrained setting often prescribe antibiotics empirically prior to or without laboratory testing to prevent severe outcomes in any patient hospitalized with malaria. However, this indiscriminate use of antibiotics has been identified as the driving force for antibiotic resistance, which is already at alarming rate in malaria endemic nations. In developed countries where malaria had been previously eradicated, there are increasing reports of imported malaria with concurrent bacteraemia. In this review, we emphasized the role of malaria in the indiscriminate use of antibiotics and the fact that eliminating malaria in Africa is one of the best strategies to address the emergence and the global spread of multi-drug resistance organisms.
Keywords: malaria